Acute lymphoblastic leukemia secondary to myeloproliferative neoplasms or after lenalidomide exposure. Issue 1 (6th December 2017) - Alhuraiji, Ahmad; Naqvi, Kiran; Huh, Yang O.; Ho, Coty; Verstovsek, Srdan; Bose, Prithviraj
Key Clinical Message: Philadelphia‐negative (Ph − ) myeloproliferative neoplasms (MPN) do rarely transform to acute lymphoblastic leukemia (ALL). While causality is difficult to establish, a few cases of ALL arising after exposure to lenalidomide for registered indications (multiple myeloma, myelodysplastic syndrome with 5q deletion) have been described in the literature. Abstract : Philadelphia‐negative (Ph − ) myeloproliferative neoplasms (MPN) do rarely transform to acute lymphoblastic leukemia (ALL). While causality is difficult to establish, a few cases of ALL arising after exposure to lenalidomide for registered indications (multiple myeloma, myelodysplastic syndrome with 5q deletion) have been described in the literature.